Annelated Pyridine Bases for the Selective Acylation of 1, 2‐Diols. Issue 29 (7th March 2022) - Mayr, Stefanie; Zipse, Hendrik
Abstract: A set of 24 annelated derivatives of 4‐diaminopyridine (DMAP) has been synthesized and tested with respect to its catalytic potential in the regioselective acylation of 1, 2‐diol substrates. The Lewis basicities of the catalysts as quantified through quantum chemical calculations vary due to inductive substituent effects and intramolecular stacking interactions between side chain π ‐systems and the pyridinium core ring system. The primary over secondary hydroxyl group selectivities in catalytic acylations of 1, 2‐diol substrates depend on the size and the steric demand of the Lewis base and the anhydride reagent. Abstract : The acylation of primary over secondary hydroxyl groups in 1, 2‐ethanediols depends strongly on size effects and noncovalent interactions between the alcohol side chains and the catalysts surface.